Certolizumab pegol for the treatment of rheumatoid arthritis. Issue 4 (July 2011) - Modesto, I; Spinello, M; Nicchi, F; Cottone, M
Rheumatoid arthritis (RA) is a chronic inflammatory disease that affects the joints. The cause of RA is unknown. TNF plays a pivotal role in the pathogenesis of RA. Since the late 1990s, the development of biologic agents that target TNF-αα has revolutionized the approach to treating RA. Five inhibitors of TNF-αα are currently available for clinical use. Certolizumab pegol is a novel TNF-αα inhibitor, consisting of a humanized Fab fragment fused to a 40 KDa polyethylene glycol moiety. After a loading dose of 400 mg at weeks 0, 2 and 4, the drug is administered as maintenance therapy at 4-week intervals by subcutaneous injection. It is demonstrated that it improves the signs and symptoms of disease, quality of life and slows the progressive destruction of joints. Certolizumab pegol was generally well tolerated when used as a monotherapy or in combination with methotrexate, with most adverse events being of mild-to-moderate intensity, with a response rate similar to that of other biological therapy available for the treatment of RA. In conclusion, certolizumab pegol is an effective new option for the treatment of RA.